Effect of Stir-Frying, Boiling, and Baking on Hexaconazole Residue Levels in Welsh Onion (Allium fistulosum L.) - Myungheon Kim; Mihyun Cho; Jaebin Im; Changkyo Seo; Changhyeon Park; Moo-Hyeog Im (Foods)
Hexaconazole, a triazole insecticide, is widely used to control rust disease in Welsh onions. Residue levels of pesticides vary based on the cooking methods. Although studies on hexaconazole residue have involved vegetables such as cabbage, research on Welsh onion is limited. This study investigated the effect of different cooking methods on hexaconazole residues. Welsh onion was processed by common cooking methods such as stir-frying, boiling, and baking, and analyzed for pesticide residues using liquid chromatography with tandem mass spectrometry. The results showed that the removal rates of pesticides after cooking were 40.0–62.9% for stir-frying, 80.0–91.4% for boiling, and 51.4–77.1% for baking. Regardless of cutting thickness (0.8 cm or 5 cm), the reduction rate of pesticide residues increased with time during boiling. Increased reduction rates were also observed with increased time during baking. As stir-frying time increased, the residue amount increased due to water loss. However, the absolute amount of the pesticide decreased with increasing time. Therefore, the residue amount of hexaconazole in Welsh onion was reduced by various general cooking processes. These findings can provide a valuable foundation for research on Welsh onion processing, address consumer concerns about pesticide residues, and provide baseline data for risk assessments.